Bench scale continuous coagulation-flocculation of saline industrial wastewater contaminated by hydrocarbons. (April 2020) - Bruno, P.; Campo, R.; Giustra, M.G.; De Marchis, M.; Di Bella, G.
Abstract: This study analyzes the outcomes obtained with the treatment of coagulation-flocculation applied to industrial wastewater coming from an oil tanker. Characteristics of this wastewater are high salinity and the presence of recalcitrant pollutants predominantly of hydrocarbon origin. Therefore, the application of a chemical-physical treatment is preferred rather than biological treatment, since the simultaneous effect of salinity and hydrocarbons plays an inhibitory role in biomass growth. In coagulation-flocculation process, the first phase of coagulation aims at electrical destabilization of pollutants particles, whereas the flocculation phase allows destabilized particles to aggregate and form flakes which, then, the last phase of the process removes from effluent by sedimentation or flotation. The novelty of this experimentation consists in the optimization of the continuous wastewater treatment with advantages both economic and in terms of treatment flexibility. The observation of the continuous process has highlighted the need for a deflector element in the passage section from the flocculation to the sedimentation compartment, to guarantee the establishment of the calm conditions necessary to allow sedimentation inside the last compartment. Results' analysis has shown that the process allows high removal efficiencies of the main pollutants analyzed in this study. In particular, the removal efficiency of TSS always stood at values greater than 90 %, while the removal efficiency of TPH was even almost close to 100 %. Instead, the removal of the organic substance in terms of COD and TOC has achieved lower performances. Therefore, in the outlet wastewater the levels of the contaminants were usually lower than the limits imposed by law to allow the discharge into the receiving water body (sea). The best test was the one in which the slop fed to the system of coagulation-flocculation was previously subjected to a treatment in which the oil was removed. Furthermore, the presence of the deflector element favors the sludge settling and therefore the removal of pollutants from the clarified.